Growth and development of thigh muscle thickness and anaerobic power generation capacity in short-distance and all-round junior speed skaters - Kumagawa, D.; Tsunoda, N. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The force and power generation capacities of the lower limb muscles are improved by speed skating training in junior speed skaters (Nemoto et al. 1990, de Koning et al. 1991). However, there are differences in aerobic and anaerobic power output between shortdistance and middle- to long-distance skating (de Koning et al. 2005). Therefore, the mass and anaerobic power generation capacity of the lower limb muscles are expected to show different developmental trends during puberty between short-distance and all-around skaters. This study investigated the effects of training on the growth and development of thigh muscle thickness and power generation capacity in male Japanese junior speed skaters. Methods: Subjects were 425 male speed skaters aged 12-18 years old. They were divided into two groups according to type of skating: short-distance skaters (SS; competitive distance: 500-1000 m) and all-round skaters (AS; competitive distance: >1500 m). Thickness of the anterior thigh (MTTa), lateral thigh (MTTl), and posterior thigh (MTTp) was measured by Bmode ultrasound. Maximal anaerobic power (MAnP) was measured using a bicycle ergometer. Mean skating velocity of 500 m (SV500), calculated from recently attained individual best times, was used as a measure of skating performance. Mean values of these parameters were calculated by age, and rates of growth were calculated by differentiating these values with respect to time. Results: MTTa and MTTp were significantly larger in the SS skaters than in the AS skaters at 16 and 17 years old. MAnP and MAnP normalized by body mass were significantly higher in the SS skaters than in the AS skaters at 16-18 years old. Moreover, SV500 was higher in the SS skaters than in the AS skaters at 16-18 years old. The highest rate of growth in thigh muscle thickness was observed at 14.9-15.3 years old in the SS skaters and at 14.0-14.7 years old in the AS skaters. In the SS skaters, the highest rate of change in MAnP and SV500 was observed at 14.9 years old and 14.6 years old, respectively, almost coinciding with the highest rate of growth in muscle thickness. In the AS skaters, however, the highest rate of change in MAnP (13.0 years old) and SV500 (13.2 years old) occurred before the highest rate of growth in muscle thickness. Discussion: These findings suggest that different modes of training for speed skating have different effects on muscle mass, anaerobic power generation capacity, and 500-m skating performance after puberty in male speed skaters. Developmental trends in these three parameters nearly coincided in the SS skaters, whereas rapid growth of power generation capacity and skating performance occurred before rapid growth of muscle mass in the AS skaters.